FREQUENT COMPLICATIONS IN PATIENTS DURING HEMODIALYTIC TREATMENT - Sampaio, Richard da Silva (2021)
Objective: to identify in the literature the most important complications during hemodialysis treatment. Materials and Method: this is an integrative review of exploratory type, with a qualitative analysis of the literature found in virtual librarians. A search for scientific data in the online databases: National Library of Medicine, Latin American and Caribbean Center on Health Sciences Information, Scientific Electronic Library Online and Google Scholar, associated with specific descriptors between the years of 2015 to 2020. Results: were identified 8 articles to compose two research: Main complications that affect the patient on hemodialysis and Nursing interventions in view of the main complications identified. Final considerations: Patients with Chronic Kidney Disease undergoing hemodialysis treatment are subject to complications that may arise during sessions. However, when nursing care is properly employed, it can revert and / or stabilize the patient's condition.